Alpaca cheese: a new alternative - Larico Medina, Heinz (2018)
The objective of this study was to evaluate the possibility of making cheese from alpaca milk. The physicochemical properties of the milk were determined, as well as the yield, chemical composition, and sensorial characteristics of the cheese. Milk was obtained by manual milking of alpacas at the beginning of lactation with crias at foot, set aside 12 hours before milking. The density, Dornic acidity and Gerber fat were determined, and total and non-fat milk solids were estimated in the milk. The chemical composition of the cheese was determined by official methods of the AOAC, and the sensory characteristics of the cheese through the hedonic test on a scale of 1 to 4 with 100 panelists. Fresh milk had a density of 1.0469 ± 0.0025, acidity 16.92 ± 1.74 °D, fat 4.12 ± 0.08%, protein 6.34 ± 0.41%, total solids 16.84 ± 0.70%, solids non-fat 12.72 ± 0.63% and a cheese yield of 21.6 ± 1.9%. The chemical composition of the cheese indicated 46.5% humidity, 18.9% ash, 41.8% protein, and 24.4% fat (dry matter). The cheese was a lean product with a hard texture and pleasant for consumption.